2016
DOI: 10.1016/j.ehb.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The long-run effect of education on obesity in the US

Abstract: The proportion of obese population has been gradually increasing in the US over the past few decades. In this study I investigate how education is associated with Body Mass Index (BMI) in later stages of life. BMI, weight(kg)=height(m) 2 ; is the principle measure used for classifying people as obese. Using sibling data and methods that take account of unobserved endowments and environment shared by siblings, I …nd that there is large variation in BMI between siblings and that education is negatively associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 45 publications
2
18
1
1
Order By: Relevance
“…Studies usually include a range of parental socioeconomic conditioning factors in the estimation, arguably this controls for part of the family "environmental" factors. Evidence suggests that socioeconomic factors such as education has a long run effect on obesity (Kim 2016). Based on data from the German Socio-Economic Panel (SOEP), Coneus and Spiess (2008) estimate the intergenerational relationship of both father and mother and children.…”
Section: Evidence On Intergenerational Transmission Mechanismsmentioning
confidence: 99%
“…Studies usually include a range of parental socioeconomic conditioning factors in the estimation, arguably this controls for part of the family "environmental" factors. Evidence suggests that socioeconomic factors such as education has a long run effect on obesity (Kim 2016). Based on data from the German Socio-Economic Panel (SOEP), Coneus and Spiess (2008) estimate the intergenerational relationship of both father and mother and children.…”
Section: Evidence On Intergenerational Transmission Mechanismsmentioning
confidence: 99%
“…Some studies have found no causal effect (Amin et al, 2015;Arendt, 2005;Lundborg, 2012); others have found causal effects much smaller than a simple regression of BMI on educational attainment would imply (Brunello et al, 2013;Kenkel et al, 2006;Kim, 2016;von Hippel and Lynch, 2014); and one study found a causal effect larger than a simple regression would suggest (Grabner, 2009). These designs are improvements over approaches using only covariates to address selection.…”
Section: Introductionmentioning
confidence: 99%
“…To address how education could influence BMI, a study with siblings sharing the same environment was performed. This study demonstrated that higher education levels correlate with a lower BMI ( Kim, 2016 ). Educational level could affect the selection and purchase of healthy food due to the knowledge of healthy food ( Bhurosy and Jeewon, 2014 ).…”
Section: Obesogenic Environmentmentioning
confidence: 57%